Case Report: Sequential Liver After Kidney Transplantation in a Patient With Sensenbrenner Syndrome (Cranioectodermal Dysplasia) - Ryżko, Joanna; Walczak-Sztulpa, Joanna; Czubkowski, Piotr; Latos-Bieleńska, Anna; Kowalski, Adam; Stefanowicz, Marek; Jarmużek, Wioletta; Grenda, Ryszard; Pawłowska, Joanna (Frontiers in Pediatrics, 2022)
Sensenbrenner syndrome, also known as cranioectodermal dysplasia (CED), is a rare ciliopathy clinically characterized by congenital craniofacial, skeletal and ectodermal defects. Chronic kidney and liver insufficiency are also present in this disorder. CED is an autosomal recessive and heterogeneous genetic disease. Six genes (IFT122, WDR35,IFT140, IFT43, IFT52, and WDR19) are known to be associated with this syndrome. Until 2021 more than 70 patients have been reported with CED , however, an orthotopic liver transplantation has been reported only in one case. Here, we present a case report of sequential liver- after -kidney transplantation in a male patient affected by CED. The kidney and liver transplantation was performed at the age of 7 and 12 years, respectively. Patients with Sensenbrenner syndrome require a multidisciplinary medical management and should regularly be followed -up by hepatologists and nephrologists, as the liver and kidney diseases are the major cause of morbidity and mortality.